The Innovation of 3D Printing Application in The Making of Bone Scaffold as Spinal Tuberculosis Drug Delivery System - Wardhani, Inten Firdhausi; Hikmawati, Dyah; Putra, Alfian Pramudita; Aminatun; Parastuti, Frazna (Universitas Airlangga, 2025)
The third highest number of tuberculosis (TB) cases was found in Indonesia. In severe cases, there is a chance for this disease to happen in the spine, which is known as spinal tuberculosis. This study examined an innovation that combined 3D-printed bone scaffolds with an injectable bone substitute (IBS) in paste form. Five pore-size variations of the bone scaffolds (600, 800, 1000, 1200, and 1400) µm were printed using an FDM 3D printer and based on Polylactide Acid (PLA) filaments. Moreover, the IBS paste was produced based on nano-hydroxyapatite (nano-HA), gelatin, hydroxypropyl methylcellulose (HPMC), and streptomycin (TB drug). The FTIR test indicates some functional groups were recorded and identified as typical bonds owned by each constituent material: stretching C-H for PLA, PO43- which represented nano-HA, amine for gelatin, stretching C-OH for HPMC, and ether for streptomycin. Furthermore, various pore-size 3D-printed bone scaffolds were characterized by their porosity, resulting in a range of 55.860% to 68.017%. The result of SEM revealed that the IBS-associated scaffold still had micropores on the surface of the scaffold. These pores let the drug load in the IBS paste release, which could be proven by drug release and the anti-TB test. Moreover, this combined biomaterial was confirmed to be a non-toxic, biodegradable material. The innovation of IBS-associated 3D-printed bone scaffold for future treatment of spinal TB represents a potential breakthrough in the medical field. This technology enables localized and regulated drug delivery, reduces systemic adverse effects, and accelerates recovery. Islam considers health as part of hifdz an-nafs (protection of life), one of the primary objectives of maqasid al-shari’ah (Islamic teachings). This development underlined that such innovations are not only scientifically significant but also carry substantial shari (Islamic legal) legitimacy.